Reproductive consequences of electrolyte disturbances in domestic animals - Galeska, Elzbieta (2022)
Electrolyte balance is essential to maintain homeostasis in the body. The most crucial electrolytes are sodium (Na+), potassium (K+), magnesium (Mg2+), chloride (Cl−), and calcium (Ca2+). These ions maintain the volume of body fluids, and blood pressure, participate in muscle contractions, and nerve conduction, and are important in enzymatic reactions. The balance is mainly ensured by the kidneys, which are an important organ that regulates the volume and composition of urine, together with which excess electrolytes are excreted. They are also important in the reproductive system, where they play a key role. In the male reproductive system, electrolytes are important in acrosomal reaction and sperm motility. Sodium, calcium, magnesium, and chloride are related to sperm capacitation. Moreover, Mg2+, Ca2+, and Na+ play a key role in spermatogenesis and the maintenance of morphologically normal spermatozoa. Infertility problems are becoming more common. It is known that disturbances in the electrolyte balance lead to reproductive dysfunction. In men, there is a decrease in sperm motility, loss of sperm capacitation, and male infertility. In the female reproductive system, sodium is associated with estrogen synthesis. In the contraction and relaxation of the uterus, there is sodium, potassium, and calcium. Calcium is associated with oocyte activation. In turn, in women, changes in the composition of the follicular fluid are observed, leading to a restriction of follicular growth. Imbalance of oocyte electrolytes, resulting in a lack of oocyte activation and, consequently, infertility.